Gambaran kualitas hidup remaja perokok SMA Negeri 3 Manado di masa pandemi COVID-19 - Alan Hopni Sasube; Windy M. V. Wariki; Gustaaf A. E. Ratag (UNIVERSITAS SAM RATULANGI, 2022)
The COVID-19 pandemic has caused health and education emergencies that have an impact on the lives of teenage students, resulting in significant changes in teenage lifestyles, such as the desire to consume alcohol, cigarettes, and others. However, the most crucial impact that is felt is the creation of snoring behavior among adolescents. Smoking behavior has a negative impact on the quality of life of adolescents, which causes problems in the adolescent's environment. From this phenomenon, researchers conducted research in order to find out the picture of the quality of life of young smokers at SMA Negeri 3 Manado during the COVID-19 pandemic. This research used a quantitative descriptive with convenience sampling techniques within the limits of the inclusion criteria. The research tools used were the WHOQOL-BREF and GSHS 2015 questionnaires in electronic form. The results of the 85 respondents show that average quality of life scores include domains: physical, psychological, social relationships, and environmental, they’re all in the range of 40 to 80. The subjects of the research were an average of 15 – years – old, who has only begun smoking at age of 14 with the frequency of smoking being 10 - 29 days, and had family members who smoke cigarettes. The research conclusion is the overview of the quality of life in the physical, psychological, social relationship, and environment domains of 85 teenagers smokers mostly have the moderate quality of life.Keywords: smoking behavior, quality of life